2021
DOI: 10.51983/ajeat-2021.10.1.2802
|View full text |Cite
|
Sign up to set email alerts
|

Attack in SDN Based Distributed Denial of Service

Abstract: DOS assaults are executed with the aid of using assault tools, worms and botnets the usage of exclusive packet-transmission techniques and diverse types of assault packets to conquer protection structures. These issues cause protection structures requiring diverse detection techniques to be able to discover assaults. Moreover, DOS assaults can blend their traffics for the duration of flash crowds. By doing this, the complicated protection machine cannot locate the assault site visitors in time. In this challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Such chronic diseases give rise to a range of symptoms, such as shortness of breath, excessive mucus production, chest pain, tightness in the chest, coughing, and many more. Breast cancer is currently the most prevalent form of cancer, resulting in 685,000 fatalities worldwide 4 . Similarly, Diabetes, a chronic metabolic disease contributes to 1.5 million deaths each year 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such chronic diseases give rise to a range of symptoms, such as shortness of breath, excessive mucus production, chest pain, tightness in the chest, coughing, and many more. Breast cancer is currently the most prevalent form of cancer, resulting in 685,000 fatalities worldwide 4 . Similarly, Diabetes, a chronic metabolic disease contributes to 1.5 million deaths each year 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in response to the aforementioned issues, several researchers have proposed implementing computer-aided diagnosis, which can simplify the work of physicians and decrease the likelihood of misdiagnosis. Previous research on various CDs [4][5][6][7][8][9][10][11] has demonstrated that it is feasible to detect and categorize CDs using Machine Learning (ML) technology. However, such approaches have shown lower performances and exhibit some limitations such as imbalanced data, accuracy paradox, missing data problems, slow convergence by metaheuristic techniques like Genetic Algorithm (GA), etc.…”
Section: Introductionmentioning
confidence: 99%